Doing sensory ethnography - Pink, Sarah 1966- (Sage, 2009)
Doing Sensory Ethnography responds to a recent an explosion of interest in the senses across the social sciences. In this important and groundbreaking book, Sarah Pink suggests re-thinking the ethnographic process through reflexive attention to what she terms the 'sensoriality' of the experience, practice, and knowledge of both researchers and those who participate in their research. The book provides an accessible analysis of the theoretical, methodological, and practical aspects of doing sensory ethnography, drawing on examples and case studies from the growing literature on sensory ethnographic studies and from the author's own work. Doing Sensory Ethnography is the first book to concentrate on outlining a sensory ethnographic methodology.